Demand power with EV charging schemes considering actual data - Jun-Hyeok Kim (Journal of International Council on Electrical Engineering, 2016)
Eco-friendly energies have recently become a popular topic. Given this trend, we predict that a large number of electric vehicles (EVs) will be widely used. However, EVs need to be connected to a power system for charging, thereby causing severe risks, such as rapid increase of demand power. Therefore, in this study, we analyze the effects of EV charging on demand power, which depend on different charging schemes, namely, dumb charging, off-peak charging, time-of-use (ToU) price-based charging. For practical analysis, we conduct simulations by considering the actual power system and driving patterns in South Korea. Simulation results show that the ToU price-based charging scheme exhibits better performance in terms of demand power over the other charging schemes.